2019
DOI: 10.48550/arxiv.1912.05248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immiscible two-phase flow in porous media: Effective rheology in the continuum limit

Subhadeep Roy,
Santanu Sinha,
Alex Hansen

Abstract: It is becoming increasingly clear that there is a regime in immiscible two-phase flow in porous media where the flow rate depends of the pressure drop as a power law with exponent different than one. This occurs when the capillary forces and viscous forces both influence the flow. At higher flow rates, where the viscous forces dominate, the flow rate depends linearly on the pressure drop. The question we pose here is what happens to the linear regime when the system size is increased. Based on analytical calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…This result suggests that the onset of non-linear flow dynamics may occur at lower capillary numbers in larger samples. This assertion agrees with dynamic pore network modeling observations showing that the onset of non-linear flow regimes start at lower flow rates as system size increases (Hansen et al, 2023;Pedersen & Hansen, 2023;Roy et al, 2019).…”
Section: Core-scale Versus Pore-scale Resultssupporting
confidence: 91%
“…This result suggests that the onset of non-linear flow dynamics may occur at lower capillary numbers in larger samples. This assertion agrees with dynamic pore network modeling observations showing that the onset of non-linear flow regimes start at lower flow rates as system size increases (Hansen et al, 2023;Pedersen & Hansen, 2023;Roy et al, 2019).…”
Section: Core-scale Versus Pore-scale Resultssupporting
confidence: 91%
“…From a theoretical perspective, Sinha and Hansen (2012) suggested that the exponent a was around 0.5 and confirmed this behavior using a dynamic pore-scale model. Roy et al (2019) proposed a size dependence of the non-linear regime, such that for larger systems, the transition from intermittency to linear flow occurred for lower Ca in a high flow rate regime. In the limit of an infinite system, this suggests that there is no linear Darcy regime at all.…”
Section: Introductionmentioning
confidence: 99%